GE_GERICHTE C/25148/2012 vom 27. September 2016 - GE Cour de justice (2016)
DROIT D'ÊTRE ENTENDU ; SUSPENSION DE LA PROCÉDURE ; VISITE ; RELATIONS PERSONNELLES ; CURATEUR ; AUTORITÉ PARENTALE | CC.273.1:CC.274.2:CC.308.1:CC.308.3